S3 Guideline “Management of Patients with Non-Specific, Functional and Somatoform Physical Complaints” – What is Important for Gynaecological Practice? - Siedentopf, F.; Hausteiner-Wiehle, C. (Geburtshilfe und Frauenheilkunde, 2013)
When the guideline was compiled, the available evidence was heterogeneous; the evidence varied depending on the subject addressed and was often of only moderate quality. Nevertheless, a strong consensus was reached on almost all subjects. It is recommended that physicians develop a collaborative working relationship with the patient, focus on symptoms and coping strategies and avoid making stigmatising comments. A biopsychosocial diagnostic evaluation with a sensitive discussion of the signs of psychosocial stress allows problems of this type and co-morbid conditions to be recognised early on and reduces the risk of iatrogenic somatisation. In uncomplicated cases, establishing a biopsychosocial explanatory model and physical/social activation are recommended. More serious cases call for collaborative, coordinated management with regular appointments (as opposed to ad-hoc appointments when the patient feels worse), gradual activation and psychotherapy. The comprehensive treatment plan can be multimodal and can potentially include physical management strategies, relaxation techniques and antidepressants.
Keywords: gynaecology; somatoform physical complaints; primary psychosomatic care; chronic pelvic pain in women